De cómo reemplazar a un rey: retrato, visualidad y poder en la crisis de la independencia (1808-1830) - Majluf, Natalia (2013)
This essay proposes to explore the visual expressions of political power during the crisis of independence, in the transition from the colonial monarchical system toward the constitution of the new South American republics. We shall take as our point of departure the depersonalization of power which accompanied the fall of the king and explore the different materializations of the modernnation-state and the uncertain place which heroes’ portrait occupied in the new republican symbolic cosmos.